2012
DOI: 10.1038/labinvest.2012.103
|View full text |Cite
|
Sign up to set email alerts
|

Increased intrahepatic resistance in severe steatosis: endothelial dysfunction, vasoconstrictor overproduction and altered microvascular architecture

Abstract: Non-alcoholic fatty liver disease can progress to steatohepatitis and fibrosis, and is also associated with impaired liver regeneration. The pathophysiology remains elusive. We recently showed that severe steatosis is associated with an increase in portal pressure, suggesting liver flow impairment. The objective of this study is to directly assess total intrahepatic resistance and its potential functional and structural determinants in an in situ perfusion model. Male Wistar rats fed a control (n ¼ 30) or a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
136
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(150 citation statements)
references
References 43 publications
7
136
1
6
Order By: Relevance
“…Our results suggest the hypothesis that in patients with NAFLD, there is a reduced vascular compliance in the liver due to augmented hepatic vascular resistance to portal blood flow and an increased hepatic vascular tone that starts before the onset of fibrosis. This change was previously demonstrated by Francque et al [18] in an experimental animal model; in their study, Wistar rats fed with a methionine-and choline-deficient diet for four weeks developed severe steatosis associated with a significant increase in intrahepatic resistance before the onset of fibrosis and inflammation. These changes involved functional (liver endothelial dysfunction and vasoconstrictor overproduction) and structural (sinusoidal altered microvascular architecture) factors.…”
supporting
confidence: 73%
“…Our results suggest the hypothesis that in patients with NAFLD, there is a reduced vascular compliance in the liver due to augmented hepatic vascular resistance to portal blood flow and an increased hepatic vascular tone that starts before the onset of fibrosis. This change was previously demonstrated by Francque et al [18] in an experimental animal model; in their study, Wistar rats fed with a methionine-and choline-deficient diet for four weeks developed severe steatosis associated with a significant increase in intrahepatic resistance before the onset of fibrosis and inflammation. These changes involved functional (liver endothelial dysfunction and vasoconstrictor overproduction) and structural (sinusoidal altered microvascular architecture) factors.…”
supporting
confidence: 73%
“…KCs- derived TNF-a is mitogenic and chemoattractant for HSC (24). However, the nature of these data is still controversial (25). Tokushige et al reported a significant increase of serum TNF-a levels and altereted Th1/Th2 balance (26).…”
Section: Resultsmentioning
confidence: 99%
“…The dysfunction of LSECs is known to augment intrahepatic resistance to impair microcirculation in the liver [18,26]. In fact, increased intrahepatic resistance has been demonstrated in an isolated-perfused rat liver obtained from a cafeteria diet-fed model of NAFLD [27], a methionine-choline-deficient model of NASH [28], and from a model of LPS-induced endotoxemia [29]. While the assessment of intrahepatic micro-circulation is technically limited in mice [30], impaired blood flow in the liver may accelerate hepatocyte cell death in hypoxic micro-environments.…”
Section: Discussionmentioning
confidence: 99%